A force-velocity relationship and coordination patterns in overarm throwing - van den Tillaar, R.; Ettema, G. (Journal of Sports Science & Medicine, 2004)
A force-velocity relationship in overarm throwing was determined using ball weights varying from 0.2 to 0.8 kg. Seven experienced handball players were filmed at 240 frames per second. Velocity of joints of the upper extremity and ball together with the force on the ball were derived from the data. A statistically significant negative relationship between force and maximal ball velocity, as well as between ball weight and maximal ball velocity was observed. Also, with increase of ball weight the total throwing movement time increased. No significant change in relative timing of the different joints was demonstrated, suggesting that the subjects did not change their "global "coordination pattern (kinematics) within the tested range of ball weights. A simple model revealed that 67% of ball velocity at ball release was explained by the summation of effects from the velocity of elbow extension and internal rotation of the shoulder. With regard to the upper extremity the internal rotation of the shoulder and elbow extension are two important contributors to the total ball velocity at release.